ضوابط الكسب الحلال عبر المنصات الرقمية: دراسة فقهية تحليلية في عصر اقتصاد المنصات: Limitations of Making a Halal Livelihood through Digital Platforms: An Analytical Fiqh Study in the Platform Economy Era - Itsnaini Bambang Hasto Nugroho; Isman Isman (Universitas Muhammadiyah Surakarta, 2025)
This research aims to explore the sharia principles that govern economic activities in the